2016
DOI: 10.1016/j.joca.2016.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Role of thigh muscle cross-sectional area and strength in progression of knee cartilage degeneration over 48 months – data from the Osteoarthritis Initiative

Abstract: Objective To determine in a 48-month longitudinal study the association of thigh muscle cross-sectional area (CSA) and strength on progression of morphologic knee cartilage degeneration using 3T magnetic resonance imaging (MRI). Design Seventy Osteoarthritis Initiative (OAI) subjects aged 50-60 years, with no radiographic evidence of osteoarthritis (OA) and constant muscle strength over 48 months as measured by isometric knee extension testing were included. Baseline right thigh muscle CSAs were assessed on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 43 publications
0
31
0
Order By: Relevance
“…In addition, 46% of the included studies did not control the physical activity level as a potential confounding variable (Goldman et al. ) between the patients with LBP and asymptomatic participants. Therefore, the results of some included studies (Dangaria & Naesh, ; Arbanas et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, 46% of the included studies did not control the physical activity level as a potential confounding variable (Goldman et al. ) between the patients with LBP and asymptomatic participants. Therefore, the results of some included studies (Dangaria & Naesh, ; Arbanas et al.…”
Section: Discussionmentioning
confidence: 99%
“…Dangaria & Naesh (1998) demonstrated that there is a significant relationship between a reduction in the CSA of the psoas major muscle and the duration of continuous sciatica of the affected leg (Spearman's q = 0.8; P = 0.05). In addition, 46% of the included studies did not control the physical activity level as a potential confounding variable (Goldman et al 2016) between the patients with LBP and asymptomatic participants. Therefore, the results of some included studies (Dangaria & Naesh, 1998;Arbanas et al 2013;Abbas et al 2016;Hyun et al 2016;Singh et al 2016) could be confounded by this potentially important factor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is therefore important to include a skyline view X-ray in order to detect osteophytes and joint space narrowing of the PF joint. In a recent systematic review of studies evaluating the prevalence of radiographic PF OA, it was found that most included studies used lateral and/or skyline views to define PF OA [12]. Some studies have used these two views in the supine position with the knee flexed to 45 degrees [10], while others have used weight bearing radiographs with 30 degrees of knee flexion for the lateral views and non-weight bearing skyline view radiographs with knees in 30 degrees flexion [4].…”
Section: Imaging Definitionmentioning
confidence: 99%
“…Possible risk factors for progressive loss of patellar cartilage were age, BMI and more severe pain scores at baseline. [62,63] There is also a suggestion that exercise is associated with less patellar cartilage deterioration [12,61]. Known risk factors for progression of OA (woman, age, BMI) have shown to be risk factors for progression of PF cartilage deterioration.…”
Section: Othermentioning
confidence: 99%